Primary hypertrophic osteoarthropathy: genetics, clinical features and management - Lu, Qi; Xu, Yang; Zhang, Zeng; Li, Shanshan; Zhang, Zhenlin (Frontiers in Endocrinology, 2023)
Primary hypertrophic osteoarthropathy (PHO) is a genetic disorder mainly characterized by clubbing fingers, pachydermia and periostosis. Mutations in the HPGD or SLCO2A1 gene lead to impaired prostaglandin E2 (PGE2) degradation, thus elevating PGE2 levels. The identification of the causative genes has provided a better understanding of the underlying mechanisms. PHO can be divided into three subtypes according to its pathogenic gene and inheritance patterns. The onset age, sex ratio and clinical features differ among subtypes. The synthesis and signaling pathways of PGE2 are outlined in this review. Cyclooxygenase-2 (COX-2) is the key enzyme that acts as the rate-limiting step for prostaglandin production, thus COX-2 inhibitors have been used to treat this disease. Although this treatment showed effective results, it has side effects that restrain its use. Here, we reviewed the genetics, clinical features, differential diagnosis and current treatment options of PHO according to our many years of clinical research on the disease. We also discussed probable treatment that may be an option in the future.